The exodus theme in the Old and New Testament - Sheriffs, Deryck C T (Rhodes University, Faculty of Divinity, Department of Divinity, 1967)
The best starting point for an examination of the theme and theology of the Exodus in the Old Testament is the Psalter, for here is recorded the living faith of Israel over a long period. The compilation of the Psalter from its earliest poems to its latest additions and final editing spans several centuries. It is a collection of collections, revised and edited more than once. Most scholars today agree that its material ranges in date from pre-exilic to late post-exilic, there being a swing away from an extravagant preference for a Maccabean dating of many Psalms. The Exodus theme to be found in the Psalter thus falls within a broad historical sweep. In the Psalter, individual and communal expressions of faith both have their place. Personal Psalms lay bare the human heart with the gamut of its emotions from despair to deep joy and praise. Psalms which were used corporately draw together the worshiping community in a way which reveals the unity of Israel, the nation, to be founded upon their relationship to Yahweh. Into the fabric of individual and national life, the thread of the Exodus faith was woven. Our task is to follow this thread, and discover the pattern which it weaves against its background. In the analysis which follows, each of the five Books of the Psalter will be examined in turn, the important passages being dealt with first, then the oblique references to the Exodus, and, lastly, those which may be described as conjectural. There are some nine Psalms which deal directly with the Exodus and the wilderness wanderings ... Chap. 1, p. 1.
Keywords: Bible; Exodus, The -- History of doctrines